Resolved Stellar Mass Estimation of Nearby Late-type Galaxies for the SPHEREx Era: Dependence on Stellar Population Synthesis Models - Jeong Hwan Lee; Minjin Kim; Taehyun Kim; Hyunjin Shim; Luis C. Ho; Ho Seong Hwang; Hyunmi Song; Dohyeong Kim; Yujin Yang; Woong-Seob Jeong (The Astronomical Journal)
The upcoming all-sky infrared spectrophotometric SPHEREx mission is set to provide spatially resolved stellar mass maps of nearby galaxies, offering more detailed insights than integrated light observations. In this study, we develop a strategy for estimating stellar mass using SPHEREx by examining the dependence on different stellar population synthesis (SPS) models and proposing new scaling relations based on simulated SPHEREx data. We estimate the resolved stellar masses of 19 nearby late-type galaxies from the PHANGS-MUSE survey, treating these as fiducial masses. By testing four SPS models covering infrared wavelengths, i.e., E-MILES, Bruzual & Charlot (BC03), Charlot & Bruzual (CB19), and FSPS, we find systematic differences in mass-to-light ratios at 3.6 μ m ( M _* / L _3.6 _μ _m ) among the SPS models. In particular, BC03 and CB19 yield mass-to-light ratios on average  ∼0.2−0.3 dex lower than those from E-MILES and FSPS. These mass-to-light ratios strongly correlate with stellar age, indicating a significant impact of young stellar populations on stellar mass measurements. Our analysis, incorporating fiducial masses and simulated SPHEREx data, identifies the 1.6 μ m band as the optimal wavelength for stellar mass estimation, with the lowest scatter (0.15−0.20 dex) of the stellar mass. This scatter can be further reduced to 0.10−0.12 dex across all SPS models by incorporating optical and SPHEREx colors. These results can provide guidance for measuring the stellar masses of the numerous nearby galaxies that SPHEREx will survey.